IMPROVING SCIENTIFIC LITERACY AND CREATIVITY THROUGH PROJECT BASED LEARNING - Munawaroh, Rosyidatul; Rusilowati, Ani; Fianti, Fianti (Universitas Negeri Semarang, 2018)
This research aims are to investigate the assesment of implementation of Project Based Learning in the material of Dynamic Fluid, to compare the value of scientific literacy and creativity between props group and poster group, and to analyze the relationship of scientific literacy and creativity of students. The research design used Mixed Method of Sequential Explanatory types. The sample is students of class XI-IPA SMA Muhamadiyah 3 Kayen, 25 students of the school year 2016/2017. The project in one class was divided into two, i.e. preparing props of principle and Bernoulli law, and preparing poster of principle and Bernoulli law. Students with props project was more active in scientific literacy activities and creative than student with the poster project. Based on the classical exhaustiveness test, the implementation of Project Based Learning with props project and the poster project has not been effective to improve the scientific literacy but it is effectively used to improve the creativity. The correlation test results show that there is no significant correlation between scientific literacy and creativity. Sustainable learning by making scientific approaches using scientific methods is needed to improve scientific literacy skills.